Variety of themes and ideas in O. Henry's work - Nasridinova, Sitora (The Lingua Spectrum, 2025)
This article explores the thematic and ideological diversity in O. Henry’s short stories. It highlights the distinctive features of the short story genre, such as its concise narrative structure, irony, and unexpected endings. The author analyzes how O. Henry’s works reflect the American mentality, cultural values, and social issues, emphasizing his contribution to the development of the American short story tradition.